Dampak Latihan Double-Leg Tuck Jump dan Knee Tuck Jump Terhadap Peningkatan Power Tungkai - Hidayat, Muhamad Syarief; Ropi, Ucu Abdul; Primadani, Dikdik (Universitas Galuh, 2022)
The purpose of this research was how much the program results in the double-leg tuck jump and knee tuck jump groups on positive changes in leg power. The experimental method was used in this research. The population of this research was at SMP Negeri 8 Tasikmalaya City with the number of students being used as research, namely 20 students. The instrument test used was the vertical jump test. The results of statistical data analysis are as follows: 1. There was a positive change from the double-leg tuck group to leg power. 2. There was a positive change from the knee tuck jump group to leg power. 3. The difference was very large in the double-leg tuck jump and knee tuck jump groups as a result of the vertical jump test. The conclusion is that the double-leg tuck jump and knee tuck jump groups have a positive impact. Suggestion: It was hoped that there will be further plyometric research as one of the recommendations in providing coaching and training for the power of the two limbs.Tujuan penelitian ini seberapa besar hasil program kelompok double-leg tuck jump dan knee tuck jump pada perubahan positif pada power tungkai. Metode eksperimen digunakan pada penelitian ini. Populasi penelitian ini di SMP Negeri 8 Kota Tasikmalaya dengan jumlah yang dijadikan penelitian yaitu 20 orang siswa. Tes awal dan tes akhir yang dipergunakan yaitu vertical jump test. Hasil analisis data statistika adalah sebagai berikut: 1. Adanya perubahan secara positif dari kelompok double-leg tuck terhadap power tungkai. 2. Adanya perubahan secara positif dari kelompok knee tuck jump terhadap power tungkai. 3. Perbedaan terlihat sangat besar kelompok double-leg tuck jump dan knee tuck jump hasil dari tes vertical jump. Kesimpulannya bahwa kelompok double-leg tuck jump dan knee tuck jump memiliki dampak yang positif pada hasil tes power tungkai. Saran: Diharapkan adanya penelitian pliometrik lanjutan sebagai salah satu rekomendasi dalam memberikan pembinaan dan pelatihan daya ledak otot bagian ke-dua tungkai.